Macraes Orogenic Gold Deposit (New Zealand) Origin and Development of a World Class Gold Mine - Craw, Dave; MacKenzie, Doug (SpringerBriefs in World Mineral Deposits, 2016)
This book describes the nature and origin of the Macraes gold deposit. It also documents the key features of this spectacular deposit for a wide range of professionals in the resource geology community. This world-class gold deposit has been a spectacular geological and economic success story, as it has developed from a small historical gold mine in discontinuous quartz veins measuring only meters to a large-scale mine in deposits spreading over kilometres in extensive disseminated gold-bearing rock.